Outcomes of endoscopic ultrasound-guided transmural drainage for postoperative peripancreatic fluid collection with an external drainage-based approach - Jun Noda; Yuichi Takano; Naoki Tamai; Masataka Yamawaki; Tetsushi Azami; Fumitaka Niiya; Fumiya Nishimoto; Masatsugu Nagahama (BMC Gastroenterology)
Abstract Background Endoscopic ultrasound-guided transmural drainage (EUS-TD) is widely performed to treat postoperative peripancreatic fluid collection (POPFC). Recent reports on EUS-TD lack a consensus on stent selection. This study aimed to assess the efficacy of EUS-TD for POPFC using an external drainage-based approach. Methods We retrospectively examined the medical records of patients with POPFC treated with EUS-TD using external drainage from October 2016 to July 2024. Technical success was defined as successful placement of the external drainage. Clinical success was defined as the reduction in fluid collection, as evidenced by follow-up computed tomography 1 week post-procedure. Results This study included 14 patients. The median duration from surgery to endoscopic treatment was 13 (range: 11–26) days. The median procedural time was 26 (range: 13–35) min. The technical success rate was 100%, and 6 Fr endoscopic nasocystic drainage was performed in all patients. The clinical success rate was 100%, and no adverse events were observed. One patient experienced self-removal and required repuncture. Conclusions EUS-TD for POPFC with an external drainage-based approach is safe and effective, with a short procedure time. However, this was a retrospective study with a small sample size, suggesting that future prospective studies are warranted.